Sealing Performance Layered Metal Gasket Based on the Simulation Method - Karohika, I Made Gatot; Haruyama, Shigeyuki; Antara, I Nyoman Gde; Budiarsa, I Nyoman; Penindra, I Made Dwi Budiana (TEKNIK, 2020)
Studies for corrugated metal gaskets are still ongoing to improve its performance. This is considered to be a single gasket with SUS304 material when contact with flanges that have greater surface roughness, reduced contact width and plastic deformed contact surfaces are incomplete and cannot fill the surface roughness of flanged flanges. The use of softer material than the base material as a surface covering material is used to improve the performance of the gasket. In this study, therefore the effect of modulus of elasticity ratio and thickness ratio on contact width and contact stress, 25A three-layer metal gasket was investigated using Finite Element Analysis. The results showed that the material with tangent modulus, Ehal = Eal / 150 had the highest slope for contact width. While the contact width of the plastic mode gasket is higher than the elastic mode gasket.